Transcriptome Sequencing of the Pale Anemones (Exaiptasia diaphana) Revealed Functional Peptide Gene Resources of Sea Anemone - Fu, Jinxing; He, Yanbin; Peng, Chao; Tang, Tianle; Jin, Aihua; Liao, Yanling; Shi, Qiong; Gao, Bingmiao (Frontiers in Marine Science, 2022)
Sea anemone venom is a marine drug resource library with pharmacological and biotechnology value, and it contains complex and diverse functional peptide neurotoxins. However, the venom components of only a limited number of sea anemone species have been globally evaluated by transcriptomics and proteomics. In this study, 533 putative protein as well as peptide toxin sequences were found on a large scale from dissimilar developmental stages of sea anemone Exaiptasia diaphana, which can be divided into 75 known superfamilies according to the predicted functions. Among them, the proportion of protein is 72.98%, and its main families are metalloproteases, chymotrypsinogen like, collagen, pancreatic lipase-associated protein like, and G-protein coupled receptor, while the proportion of peptides is 27.02%, and main families are ShK domain, thrombin, Kunitz-type, defensin, as well as insulin-like peptide. Finally, typical anemone peptide neurotoxins were screened, and the 3D structure and pharmacological activity of these anemone peptide neurotoxins were predicted by homology modeling. We elucidate on a valuable high-throughput approach for obtaining sea anemone proteins and peptides. Our findings form the basis for targeted studies on the diversity as well as pharmacological effects of sea anemone peptide neurotoxins.